Free field world-sheet correlators for AdS3 - Dei, Andrea; Gaberdiel, Matthias R.; Gopakumar, Rajesh; Knighton, Bob (The journal of high energy physics, 2021)
A bstract We employ the free field realisation of the psu 1 1 2 1 world-sheet theory to constrain the correlators of string theory on AdS 3 × S 3 × 𝕋 4 with unit NS-NS flux. In particular, we directly obtain the unusual delta function localisation of these correlators onto branched covers of the boundary S 2 by the (genus zero) world-sheet — this is the key property which makes the equivalence to the dual symmetric orbifold manifest. In our approach, this feature follows from a remarkable ‘incidence relation’ obeyed by the correlators, which is reminiscent of a twistorial string description. We also illustrate our results with explicit computations in various special cases.